2019
DOI: 10.1002/uog.20171
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sylvian fissure angle as early sonographic sign of malformation of cortical development

Abstract: Objective To evaluate Sylvian fissure development by assessing Sylvian fissure angles in fetuses with malformation of cortical development (MCD). Methods This was a retrospective study of 22 fetuses with MCD. Cases with a stored three‐dimensional (3D) brain volume acquired at 18 + 0 to 30 + 6 weeks of gestation at an ultrasound‐based research clinic between January 2010 and December 2017 were identified through a database. Of the 22 fetuses, seven had an extracranial abnormality, such as cardiac, renal, gastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 17 publications
3
35
0
2
Order By: Relevance
“…Gindes et al demonstrated that the sylvian fissure grows asymmetrically in an anterior-posterior direction rather than laterally or in the inferior-superior direction. Very recently, reference charts of the sylvian fissure angle obtained in strictly coronal views have been published [20], giving early hints towards delayed development seen in most cortical malformations [19]. Our data corroborate and further specify the time pattern of CNS folding because we had 100% visualization of the lateral sulcus and the ongoing process of operculization at 20 completed weeks.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Gindes et al demonstrated that the sylvian fissure grows asymmetrically in an anterior-posterior direction rather than laterally or in the inferior-superior direction. Very recently, reference charts of the sylvian fissure angle obtained in strictly coronal views have been published [20], giving early hints towards delayed development seen in most cortical malformations [19]. Our data corroborate and further specify the time pattern of CNS folding because we had 100% visualization of the lateral sulcus and the ongoing process of operculization at 20 completed weeks.…”
Section: Discussionsupporting
confidence: 81%
“…Accordingly, an accurate grading of the time-dependent cortical folding for other primary fissures such as the parietooccipital fissure, calcarine fissure, and the cingulate sulcus is feasible with obligate visualization from 23 and 24 weeks onward [1,5]. There are also technical issues in the comprehensive assessment of the sylvian fissure in the same cutting plane and a lack of standardization in both plane reconstruction and the quantification of spatial-cerebral relationships [19]. In 2015, two publications reported the reliability of multiplanar 3D ultrasounds for systematic (longitudinal) assessments of cortical differentiation, confirming prior studies [2,6,9,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…They can be difficult to see on prenatal ultrasound and are best evaluated by MRI, performed in the late second or early third trimester (after 20‐22 wk) . Recent studies have suggested that an abnormal shape and size of the sylvian fissure in early pregnancy can be an early sign of migration abnormalities and indication for further imaging by ultrasound and MRI at a later gestational age . The most common location is in the bilateral perisylvian region, but they can be unilateral and have an anterior‐posterior or posterior‐anterior gradient.…”
Section: Postmigrational Defects: Disorders Of Cortical Disorganizationmentioning
confidence: 99%
“…Previous studies have addressed the problem of quantifying sonographically the process of opercularization and formation of the Sylvian fissure. 7,12,14,15,17 The normal values of the distance between the inner calvarium and the insula have been previously published. 15,17 However, we object that this is an indirect measurement of the Sylvian fossa, because it includes the subarachnoid space, which is variable in size and distribution.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%